Increasing Student's Learning Interest in Geography Through out Door Study Method - Suhadi Rahman; Yurni Suasti; Ernawati Ernawati (Postgraduate School, Universitas Negeri Padang, 2021)
There are still many students who are less motivated to do the assignments given when studying theory and practicum, both those given in class and those that are used as homework. The learning process will be more optimal if we can take advantage of the media around us. The purpose of this research is the use of outdoor study methods or methods outside the lecture room can increase student interest in attending lectures so that the objectives of the lecture can be achieved. The method in this study using classroom action research was carried out in 3 (two) cycles, each cycle consisting of 2 meetings, each meeting time of 3 x 55 minutes. The population in the study of the Senior High School 1 Tanjung Jabung Barat. The research sample was in classes XII IPS 3 and XI IPS 4. The results showed that the outdoor study method was successful in increasing interest in learning, as seen by students being more enthusiastic in learning, more efficient, and effective, especially in geography.